Technical and Economic Feasibility of Using Solar Energy to Provide Heat Load to a Poultry House - M. Jalali; A. Banakar; B. Farzaneh; M. Montazeri (Journal of Agricultural Machinery, 2023)
IntroductionIn the poultry industry, reducing energy consumption is essential for reducing costs. Energy requirements in the poultry industry include heating, cooling, lighting, and power line energy. Identifying factors that increase energy usage is crucial, and providing appropriate solutions to reduce costs and energy consumption is inevitable. One of the major and expensive factors in the poultry industry is the use of fossil fuels, which also causes pollution. Energy costs directly impact the cost of production and increase the per capita cost of production in the meat and egg sectors. In Iran, poultry farms are among the most widely used energy consumers, especially for heating breeding halls, making them a significant subset of the agricultural sector.Materials and MethodsThe problem under study is the thermal simulation of a meat poultry farm located in Ardestan city, Isfahan province. Ardestan city is situated in a desert region in the north of Isfahan province, at a latitude of 33 degrees and 23 minutes north, and a longitude of 52 degrees and 22 minutes east. The dimensions of the poultry hall floor are 5 meters by 8 meters, and it has a capacity of 300 poultry pieces. There are two inlet air vents (windows), each with dimensions of 1.90 by 1.6 meters. The roof has an average height of 2.5 meters and is sloping, made from a combination of plastic carton, fiberglass, and sheet metal.To reduce energy consumption in this poultry farm, a solar heating system is designed and studied in this research. The farm is one of the functions of Isfahan province, with dimensions of 8 meters in length and 5 meters in width. The simulation is performed using TRNSYS software.Results and DiscussionThe results demonstrate that a collector surface area of 26 m2 is necessary to reach the technically optimal point, where the sun's maximum production is achieved with no energy dissipation. Furthermore, the findings indicate that a balance of 16 m2 is required to align the solar system with the auxiliary system.ConclusionBy installing 2 square meters of solar collectors, 5.2% of the total energy demand can be met with solar energy. To fully meet the energy demand using solar energy, a collector area of 30 square meters is required. As the solar fraction increases, the system's ability to extract solar energy also increases. The maximum production of solar energy without any wastage is achievable with a collector area of 26 square meters. Moreover, to maintain a balance between the use of solar energy and the auxiliary system, a collector area of 16 square meters is needed.